Antibacterial activity of the novel oxazolidinone contezolid (MRX-I) against Mycobacterium abscessus - Gao, Shan.; Nie, Wenjuan.; Liu, Lina.; Su, Lei.; You, Yingxia.; Geng, Ruixue.; Chu, Naihui (Frontiers in Cellular and Infection Microbiology, 2023)
Objective To evaluate contezolid (MRX-I) antibacterial activity against Mycobacterium abscessus in vitro and in vivo and to assess whether MRX-I treatment can prolong survival of infected zebrafish. Methods MRX-I inhibitory activity against M. abscessus in vitro was assessed by injecting MRX-I into zebrafish infected with green fluorescent protein-labelled M. abscessus. Thereafter, infected zebrafish were treated with azithromycin (AZM), linezolid (LZD) or MRX-I then maximum tolerated concentrations (MTCs) of drugs were determined based on M. abscessus growth inhibition using one-way ANOVA. Linear trend analysis of CFU counts and fluorescence intensities (mean ± SE values) was performed to detect linear relationships between MRX-I, AZM and LZD concentrations and these parameters. Results MRX-I anti-M. abscessus minimum inhibitory concentration (MIC) and MTC were 16 μg/mL and 15.6 μg/mL, respectively. MRX-I MTC-treated zebrafish fluorescence intensities were significantly lower than respective LZD group intensities (whole-body: 439040 ± 3647 vs. 509184 ± 23064, p < 0.01); head: 74147 ± 2175 vs. 95996 ± 8054, p < 0.05). As MRX-I concentration was increased from 0.488 μg/mL to 15.6 μg/mL, zebrafish whole-body, head and heart fluorescence intensities decreased. Statistically insignificant differences between the MRX-I MTC group survival rate (78.33%) vs. corresponding rates of the 62.5 μg/mL-treated AZM MTC group (88.33%, p > 0.05) and the 15.6 μg/mL-treated LZD MTC group (76.67%, p > 0.05) were observed. Conclusion MRX-I effectively inhibited M. abscessus growth and prolonged zebrafish survival when administered to M. abscessus-infected zebrafish, thus demonstrating that MRX-I holds promise as a clinical treatment for human M. abscessus infections.